Critical Care Sedation (Springer International Publishing, 2018)
This book provides a practical and comprehensive guide to delivering analgesia and sedation to critically ill patients for professionals and caregivers being involved in the management of these patients. It discusses and explains in detail the advantages and limitations of each drug and device using clear flowcharts, diagrams and tables. Furthermore, it explores the new drugs and - above all - new sedation delivery systems, particularly those for administering volatile anesthetics on ICUs. Written by respected experts in the field, this book is a valuable and practical resource for anesthesists, intensivists and emergency physicians interested in sedation.